POLITIK HUKUM PIDANA DALAM MELINDUNGI HAK BERSERIKAT DARI TINDAKAN UNION BUSTING (PASAL 28 UU NO 21 TAHUN 2000) - Ryan Fadly Ramadhan; Mahmud Mulyadi; Agusmidah Agusmidah (Smart Education, 2025)
Abstract: The right to associate is a constitutional right. In the context of employment, the existence of trade unions is an important instrument in fighting for workers' rights. However, in practice, freedom of association is often disrupted by union busting, which is a systematic effort made by certain parties to prevent the formation or continuation of trade unions. Union busting is carried out in various ways that are detrimental to workers' right to associate Based on Article 28 of Law No. 21 of 2000. The method used in this writing is the normative legal research method, which is a method that refers to legal norms carried out by means of literature studies related to the problems studied, this research is descriptive in nature, and the data is analyzed qualitatively. criminal law policy needs to be directed to formulate policies with formulations against Article 28 of Law No. 21 of 2000 to be more comprehensive and cover various forms of actions to obstruct freedom of association that are increasingly complex and varied, in addition, there is a need to strengthen constitutional protection of freedom of association by increasing the capacity of law enforcement officers, clarifying the boundaries between the criminal and industrial realms, and strengthening labor supervision so that workers' rights are protected in accordance with the 1945 Constitution.Keyword: Criminal Law Politics, Right to Association, Union BustingÂ Abstrak: Hak berserikat merupakan hak konstitusional. Dalam konteks ketenagakerjaan, keberadaan serikat pekerja menjadi instrumen penting dalam memperjuangkan hak-hak pekerja. Namun, dalam praktiknya, kebebasan berserikat kerap kali terganggu oleh tindakan union busting, yaitu upaya sistematis yang dilakukan oleh pihak-pihak tertentu untuk menghalangi pembentukan atau keberlangsungan serikat pekerja. Union busting dilakukan dengan berbagai cara yang merugikan hak berserikat pekerja Berdasarkan Pasal 28 Undang-Undang No. 21 Tahun 2000. Metode yang digunakan dalam penulisan ini adalah metode penelitian yuridis normatif, yaitu metode yang mengacu pada norma-norma hukum yang dilakukan dengan cara studi kepustakaan yang berkaitan dengan permasalahan yang diteliti, penelitian ini memiliki sifat deskriptif, serta data yang dianalisis secara kualitatif.Â kebijakan politik hukum pidana perlu diarahkan untuk merumuskan kebijakan dengan formulasi terhadap pasal 28 Undang-undang No. 21 Tahun 2000 agar lebih komprehensif dan mencakup berbagai bentuk tindakan penghalangan kebebasan berserikat yang semakin kompleks dan variatif selain itu, perlunya memperkuat perlindungan konstitusional kebebasan berserikat melalui peningkatan kapasitas aparat penegak hukum, kejelasan batas antara ranah pidana dan industrial, serta penguatan pengawasan ketenagakerjaan agar hak-hak pekerja terlindungi sesuai UUD 1945.Â Kata Kunci: Politik Hukum Pidana, Hak Berserikat, Union Busting